Narrative in the Arabic Translation of Children’s Literature: An Analytical Study of Two Selected Novels - Hussain Naima , Lect. Ibtisam; Salih Fenjan, Assist. Prof . Sahab (Basra studies journal, 2026)
This study explores the narrative techniques employed in Arabic translations of two 19th-century English novels adapted for children specifically Bram Stoker’s Dracula and Mark Twain’s The Adventures of Tom Sawyer. The study investigates the cross-cultural and intertemporal adaptation challenges of by analyzing 21st century Arabic translations of these works. It focuses on the way that narrative structures are modified to bring into line with the target culture’s values, linguistic norms, and the specific conventions of children’s literature. The study provides a critical evaluation of translator decisions and highlights frequent errors and systematic deviations from the source texts. Eventually, the results aim to offer guidance for future translators of children's literature, while suggesting further research into the English translation of Iraqi women's literature to explore temporally and spatially shifting feminist perspectives.